Hands On PLC Programming with RSLogix 500 and LogixPro - Kamel, Eman; Kamel, Khaled (McGraw-Hill's AccessEngineering, 2016)
Master the art of PLC programming and troubleshooting Program, debug, and maintain high-performance PLC-based control systems using the detailed information contained in this comprehensive guide. Written by a pair of process automation experts, Hands-On PLC Programming with RSLogix 500 and LogixPro lays out cutting-edge programming methods with a strong focus on practical industrial applications. Homework questions and laboratory projects illustrate important points throughout. A start-to-finish capstone design project at the end of the book illustrates real-world uses for the concepts covered. Inside: Introduction to PLC control systems and automation Fundamentals of PLC logic programming Timer and counter programming Math, move, comparison, and program control instructions HMI design and hardware configuration Process control design and troubleshooting Instrumentation and process control Analog programming and advanced control Comprehensive case studies